Pemanfaatan Tepung Tulang Ikan untuk Bidang Pertanian oleh Masyarakat Desa Tanjung Keramat Gorontalo - Desi Arisanti; Ika Okhtora Angelia; Amiruddin Amiruddin (Jurnal Ilmiah Pangabdhi, 2021)
Tuna fish bones are by-products or waste from fisheries. Not many people have applied tuna fishbone in agriculture. In fact, tuna fish bones can be used as organic fertilizer and animal feed which can be processed into bone meal. According to this condition, the Community Service Team from the Agricultural Product Technology Study Program took the initiative to assist the community to take advantage of it. This activity is carried out in Tanjung Kramat Village, which is one of the largest tuna producing areas in Gorontalo. This activity includes material presentation, discussion and demonstration of making fish bone meal. From the results of these activities, enthusiasm from the community and local village officials can be seen to develop it into organic fertilizer and animal feed.